Settlement of Breach of Contract in Cooperation and Capital Between Harsana and CV. Aasmaa Tradexindo - Puteri Syahmita (Justice Voice, 2025)
Breach of contract (wanprestasi) refers to the debtor’s negligence, resulting in the failure to fulfill obligations agreed upon in a contract. If one party fails to perform actions that are neither their rights nor obligations under the agreement, such negligence may lead to a lawsuit in court. This study addresses two research questions: 1) Why does a breach of contract occur in the implementation of the cooperation and capital agreement between Harsanah and CV. Aasmaa Tradexindo, based on Decision No. 979/Pdt.G/2022/PN.Jkt.Sel? 2) What are the legal considerations made by the panel of judges in deciding the case regarding the cooperation and capital agreement between Harsanah and CV. Aasmaa Tradexindo, based on Decision No. 979/Pdt.G/2022/PN.Jkt.Sel? The analysis uses a normative juridical approach with qualitative data collection based on a case study of Decision No. 979/Pdt.G/2022/PN.Jkt.Sel. The results of the study show that the Defendant’s failure was due to an inability to fulfill the obligations agreed upon in the written contract. The dispute was initially attempted to be resolved through negotiation, but due to the lack of an agreement, it proceeded to the civil court. In this case, the judge ruled that a breach of contract had occurred and upheld part of the Plaintiff’s claims, particularly regarding material compensation. However, the judge rejected the request for immaterial damages amounting to IDR 5,000,000,000 and a fine (dwangsom) due to insufficient evidence.